ALLELOPATHY BETWEEN LEGUMINOUS TREE AND COWPEA - SANTOS, Ceália Cristine; SILVA, Levy Geralte; SILVA, Gilvânia Campos; FERRAZ JUNIOR, Altamiro Souza de Lima (Scientia Agraria, 2010)
The knowledge of the interactions between leguminous tree and crops is of great importance to manage agroforests systems. This work evaluates the effect of leaves and roots aqueous extract of leucaena (Leucaena leucocephala) and pigeon pea(Cajanus cajan) in of cowpea seeds germination and the possibility of the humic substances revert these inhibitory effects. In this sense were carried two experiments, in the first the treatments appear the aqueous extract of leaves and roots of leucaena and pigeon pea at 0, 2, 4, 6, 8 and 10% (v/v); in the second appear the root aqueous extract of guandu e leucaena in 5%(v/v) dosage, with humic substances at 0, 10, 20, 30 and 40% (v/v) concentrations. The aqueous extracts of leguminous leaves and roots caused reductions in the cowpea germination, being this, more dramatic when root extracts were applied. There was a quadratic effect of doses of leucena leaves and root aqueous extracts on the cowpea seeds germination The application of soil extracts containing humic substances in dosages of 20 and 30% reversed the inhibitory effect on the germination of cowpea caused by the pigeon pea root extracts, but not reversed the allelopathic effects caused by the leucaena roots aqueous extract (5% v/v).